Association between Gender and Occupation with Hypercholesterolemia Risk among Hypertension Population: A Cross-sectional Study: A Case Report - Adnan, Muhammad Luthfi; Pratama, Yanasta Yudo (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Metabolic syndrome is one of the major global health problems. Hypertension and hypercholesterolemia are indicators in the diagnosis of metabolic syndrome. However, the analysis of the relationship between risk factors for hypercholesterolemia in the hypertensive population needs further study. This study aims to analyze the risk factors for hypercholesterolemia in hypertensive patients. This cross-sectional study was conducted at Depok 2 Community Healthcare Center with a focus on adult hypertensive patients. The results of blood pressure measurements, total cholesterol examinations, and participant characteristics were then analyzed using the Chi-Square test. 117 hypertensive patients were analyzed in this study with the majority being women (60.7%), elderly (70.1%), and household-based occupancy (70.1%). The majority of participants were diagnosed with grade I hypertension (53.8%) and hypercholesterolemia (59%). Women have higher risk of developing hypercholesterolemia than men (OR 3.38 (95% CI 1.555 – 7.361); p = 0.002), and non-household based occupancy were protective factor from hypercholesterolemia (OR 0.327 (95% CI 0.144 – 0.742); p = 0.008). Gender and occupation are risk factors for hypercholesterolemia in the hypertensive population. Education at the household level is needed for early detection of the risk of metabolic syndrome in the general population.